Sundown [large type] - Warren, Susan May, 1966- (Warren, Susan May, 1966- Sky King ranch, 2022)
"Former Delta Operative Colt Kingston knows when someone is lying. He may not know the truth, but he sure doesn't trust Tae, the mysterious woman his family rescued from an Alaskan blizzard. Behind those beautiful blue eyes, Colt can tell there is a troubled -- and smart -- woman. A few of her stories prove true -- they found the crashed plane and the dead body inside. Still, her tale of survival seems too incredible to believe . . . until the thugs she claims to be hunting her across Alaska show up and threaten Sky King Ranch. Now Tae must disappear, along with her secrets. Colt will have to track her down and earn her trust before it's too late. It'll take the entire family to save the world from disaster."--